STIGMA OF DISABILITY, SOCIAL PHOBIA AND SELF-ESTEEM IN ADOLESCENTS WITH PHYSICAL DISABILITY - Mushtaq, Mamoona; Anjum, Ambreen; Jameel, Rabia; Iqbal, Muhammad Nasir; Shahid, Arfah Ayesha; Dastgir, Muhammad Hamid Ahmed (Journal of Postgraduate Medical Institute, 2020)
Objective: To find out the relationship among perceived physical disability stigma, social phobia and self esteem and to explore the relationship of stigma in prediction of social phobia and self-esteem in physically disabled adolescents. Methodology: The study was conducted in Pakistan Society For The Rehabilitation Of The Disable (PSRD) high school, Ichra, Lahore, a special education institution, by using survey research design. Sample of 300 physically disabled students was taken from special education institutes. Age range of the participants was from 11 to 20 years. Postsecondary Student Survey of Disability Related Stigma (PSSDS) was used to asses stigma. Social Interaction Anxiety Scale (SIAS) was used to measure social phobia and State Self Esteem Scale (SSES) was used to assess the self-esteem of the research respondents. Results: A statistically significant correlation of perceived stigma of disability with social phobia (r = .56,, p < .001) and self-esteem (r = -.54, p < .001) was found in adolescents with physical disability. Similarly, perceived stigma turned out to be a significant positive predictor of social phobia (Î² = .40, t = 5.78, p < .001) and negative predictor for self-esteem (Î² = -.34, t = 3.64, p < .001). Results of demographic variables suggested that fathers' profession, mothers' education, monthly Income and Joint family system predicted social phobia and account for 4.2% variance in the outcome variable (R2 = .042). Amongst demographic variables, low monthly income appeared as the most significant positive predictor of social phobia (Î² = .47, t = 5.29, p < .001) and negative predictor of self-esteem (Î² = -.44, t = 3.72, p < .001). Conclusion: Perceived disability stigma is significantly correlated with social phobia and self-esteem in physically disabled adolescents.